A Study On Failure Stress and Fatigue Crack Rate Implemented to a Double Edge Notched Gusset Plate - Patty, Agnes Hanna; Yoedono, Benedictus Sonny; Murdiyanto, Danang; Herlambang , Andy Rahmadi (Jurnal Teknik Sipil, 2023)
A gusset plate is a member of a bridge structure that is significantly subjected to cyclically varying loads. It may collapse after a certain number of cycles. However a single cycle may causes structural failure although the maximum stress (due to loading) is much less than the yield or the ultimate stress of the material. In a case of notched component under such conditions, high-intensity stress will occur at the zone of the notched component. Fracture mechanics is strongly recommended in a bridge design especially for joints. It will determine the moment at which fatigue cracks will occur and how far it has propagated. This study explores a fracture phenomenon of a steel gusset plate due to fatigue loading. Modeled as a double-edged notched plate, the failure stress is found to be less than the ultimate stress of the material. By assuming that crack closure exist, the results of this study provide a significant conclusion: under a constant failure stress the rate of fatigue growth increases as the crack propagates. Keywords: Fracture mechanics, fatigue loading, stress intensity, double-edge notched